Prediction of body fat in adolescents: validity of the methods relative fat mass, body adiposity index and body fat index - Encarnação, Irismar Gonçalves (2021)
To verify the validity of anthropometric methods body adiposity index (BAI), relative fat mass (RFM) and body fat index (BFI) to estimate body fat percentage (%BF) in adolescents. Methods A cross-sectional study was carried out with 420 Brazilian adolescents aged 15–19 years, stratified by age (< 18 years, n = 356; ≥ 18 years, n = 64) and sex (boys, n = 216; girls, n = 204). The Anthropometric measurements height, body weight, hip circumference and waist circumference were collected to calculate the %BF by BAI, RFM, BFI methods. Subsequently, %BF was measured by dual emission X-ray absorptiometry (DXA), adopted as a reference method. In the statistical analysis of the data, the Pearson correlation test and the paired t test between %BF obtained by the equations and by the DXA were performed. The method validation criterion was that 68% of individuals should be within an acceptable error range of ± 3.5% of BF and Cohen's Kappa index ≥ 0.61. Additionally, the Bland–Altman graphical analysis was performed. Results All methods showed a high correlation with DXA. For the Kappa index, only the RFM reached the criterion in the total sample (0.67) and in the sample < 18 years (0.68). None of the methods reached the criterion of 68% of the sample within the error range of ± 3.5% of BF. Conclusion The BAI, RFM and BFI equations were not valid for predicting BF in the studied sample according to the criteria adopted regardless of sex or age.